2003
DOI: 10.1002/adsc.200303111
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Nitration of Phenolic Compounds

Abstract: Phenolic compounds can be nitrated by 65% nitric acid in the presence of catalytic amounts of montmorillonite KSF and bismuth(III) nitrate to give the corresponding nitrated products in good yields in a heterogeneous phase. The co-catalyst of KSF and Bi(NO 3 ) 3 can be easily recovered and reused in the next batch of nitration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Nitration is one of the most attractive and challenging process in synthetic chemistry owing the application of nitro-compounds in pharmaceuticals, agrochemicals, dyes, and polymers [73][74][75][76]. Conventionally, nitro-compounds are generated by electrophilic or nucleophilic substitutions using NO2 + or NO2 − [77][78][79]. Owing to the popularity of radical strategies in modern organic chemistry, nitration can be performed via radical processes, which represent efficient and simple tools for the conversion of C−H bonds to their C−NO2 counterparts [80][81].…”
Section: Cyclization Initiated By No2 Radicalmentioning
confidence: 99%
“…Nitration is one of the most attractive and challenging process in synthetic chemistry owing the application of nitro-compounds in pharmaceuticals, agrochemicals, dyes, and polymers [73][74][75][76]. Conventionally, nitro-compounds are generated by electrophilic or nucleophilic substitutions using NO2 + or NO2 − [77][78][79]. Owing to the popularity of radical strategies in modern organic chemistry, nitration can be performed via radical processes, which represent efficient and simple tools for the conversion of C−H bonds to their C−NO2 counterparts [80][81].…”
Section: Cyclization Initiated By No2 Radicalmentioning
confidence: 99%
“…Shi and Cui have reported that phenolic compounds can be nitrated using HNO 3 in the presence of montmorillonite KSF and Bi(NO 3 ) 3 Á5H 2 O (Scheme 156). 249 The KSF-Bi(NO 3 ) 3 Á5H 2 O mixture, which helps avoid the use of concentrated or fuming nitric acid, could be recovered and reused.…”
Section: Nitrationmentioning
confidence: 99%
“…Several different polyhydroxybenzene containing catalysts have shown catalytic activity for COCs synthesis upon CO 2 insertion [11,13,17] . Polyhydroxybenzene derivatives were mainly employed as the acidic co‐catalyst coordinating the epoxide: besides phenol, many homogeneous and heterogeneous catalysts were developed [18,19] . Pyrogallol (1,2,3‐trihydroxybenzene) based catalytic systems were first reported in seminal contributions by Kleij and co‐workers: homogeneous binary organocatalytic systems consisting of pyrogallol and tetrabutylammonium iodide (Bu 4 NI, TBAI) were active towards CO 2 insertion in terminal epoxides in very mild reaction conditions (14 examples, up to >99 % conversion, up to 94 % isolated yield; experimental conditions: T=25–45 °C, p 0 (CO 2 )=1.0 MPa, catalyst load: 2–5 mol%, solventless reaction) [20] .…”
Section: Introductionmentioning
confidence: 99%